Implementasi Metode Demonstrasi Haji dan Umrah - Muhamad Iplih (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2018)
The purpose of this study is to improve students' understanding in the material as well as the procedures for the practice of Hajj and Umrah. Implementation of learning is conducted in class X Takhassus MA Ibnul Qayyim Putri Yogyakarta in odd semester of academic year 2017/2018. In the implementation of this research outline covers four stages of activity that is planning, implementation action, monitoring, and reflection. This research is a classroom action research using observation, interview, and using demonstration method in practice of learning implementation. The result of this research is after the implementation of demonstration method, knowledge and hajj material able to build the students understanding in the practice of Hajj so that the students more easily understand the material and practice of Hajj. The learning methods undertaken to improve understanding and kepenguasaan students on the material based on the findings of researchers is a). Through the giving of materials to students b). through video presentation of the practice of performing the pilgrimage to students c). Implementation of demonstration methods implemented and practiced by students d). Evaluation of learning by teachers to students.Â